Pengaruh Latihan Depth Jump To Rimp Jump dan Box Jump dan Panjang Tungkai Terhadap Jump Shoot - Zainuddin, Erwin (Jurnal Porkes, 2022)
The purpose of this study was to analyze the effect of depth jump to rimp jump  dan box jump exercise method on jump shoot result, the difference between the influence of the limbs are long and short limbs against the results of the jump shoot and depth jump to rimp jump  dan box jump exercise interaction between the methods and the length of the legs against the results jump shoot. This research uses experimental methods with a 2 x 2 factorial design. The population in this study are atlet basket University of Tadulako of 30 people. Technique of data analysis using SPSS program 20.0. The results of the research there is a difference between the methods of exercise influence depth jump to rim jump and box jump against the results jump shoot. There is a difference between atlet  who have long and short limbs against the results jump shoot, there is interaction between the methods of exercise and long limbs against the results jump shoot. A summary of this research is the box jump is better than on the depth jump to rim jump in improving results jump shoot.